PENGEMBANGAN INSTRUMEN TES MATEMATIKA BERBASIS HIGHER ORDER THINGKING SKILLS (HOTS) UNTUK SISWA SMP - Hulwani, Almas Zati; Yuhana, Yuyu (LPPM Universitas Bina Bangsa, 2024)
The aim of this research is to develop a mathematical test instrument based on Higher Order Thingking Skills for high school students. The research methods used in this research are research and development methods or Research and Development. (R&D). The data-gathering instruments for this search are teacher lift, student perception lift, observation sheet, interview guide, and the definition test of Higher Order Thinking Skills. (HOTS). The study was tested on 25 students of the eighth grade of high school, the test was carried out on the material of linear equations and linear inequalities of one variable. The results of the research show that: 1) the test instrument Higher Order Thinking Skills developed is valid and reliable, 2) has an average difficulty level for each type of question, and 3) the test instruments Higher order thinking skills (HOTS) developed fall into the category both in different power tests. So, the tool developed by the researchers deserves to be used as an assessment to measure the Higher Order Thinking Skills (HOTS) test for high school students